2010
DOI: 10.1177/030089161009600217
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of TSPAN1 by RNA Silencing and Antisense Technique Inhibits Proliferation and Infiltration of Human Skin Squamous Carcinoma Cells

Abstract: The TSPAN1 gene might play a role in the proliferation of squamous cell carcinoma of the skin and be associated with cancer cell motility, implying a function of the gene in the development of skin cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
30
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 10 publications
(13 reference statements)
8
30
0
Order By: Relevance
“…Tspan1, a new member of the tetraspanins group, was found to be elevated in some tumors (12,(23)(24)(25). Recent studies also suggested Tspan1 gene may play a role in the proliferation of cancer cells and be associated with cancer cell motility, implying a function of the gene in the development of various cancer (12,23,26). In this study, our results revealed that Tspan1 immunopositive staining was significantly correlated with the lymph node metastasis, pTNM stages and poor prognosis of PCC.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Tspan1, a new member of the tetraspanins group, was found to be elevated in some tumors (12,(23)(24)(25). Recent studies also suggested Tspan1 gene may play a role in the proliferation of cancer cells and be associated with cancer cell motility, implying a function of the gene in the development of various cancer (12,23,26). In this study, our results revealed that Tspan1 immunopositive staining was significantly correlated with the lymph node metastasis, pTNM stages and poor prognosis of PCC.…”
Section: Discussionsupporting
confidence: 61%
“…The molecule may accept extracellular signals when located on the membrane and carry out functions in the cytoplasm, like other tetraspanins such as CD9, CD82 and CD63 (12,17,18). In the present study, we found that the expression of Tspan1 in PCC tissues was significantly higher than the normal adjacent tissues.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations